PSX-B-24 Influence of the immunomodulatory drug Azoxivet on the post-vaccination immune response in laying hens. (8th October 2021) - Sabrekova, Valentina; Korenyuga, Maxim; Konovalova, Elena; Rodionova, Natalia
Abstract: Vaccination is a primary way to prevent infectious disease in poultry. The quality of immune response depends on the immune status of the body which, in turn, depends on many endogenous and exogenous factors. This study analyzed the effect of the immunomodulatory drug Azoxivet on the immune response in laying hens after vaccination against Newcastle Disease and Infectious Bursal Disease. There were 4 groups of Loman White cross laying hens (n=20). At age 120 days, all hens habitated in individual cages with an area of 0, 15 m 2 . The conditions of keeping and feeding matched breed requirements. All groups were vaccinated against Newcastle Disease (NDV) (LaSota strain) and Infectious Bursal Disease (IBD) (Winterfield 2512 strain). All groups received Azoxivet (Az) at a dose of 0, 3 mg/kg in water three times daily. Blood sera were collected weekly for serological studies using BioChek IBD and NDV test systems. The antibody level of all hens before and after vaccination: 1378 (IBD+Az) vs. 1674, 93 (IBD) (P < 0, 05), 5194, 75 (NDV+Az) vs. 5612, 87 (NDV) (P < 0, 05). After one week of vaccination: 5931, 25 (IBD+Az) vs. 5006, 14 (IBD) (P < 0, 05), 6207, 58 (NDV+Az) vs. 5765, 21 (NDV) (P < 0, 05). Two weeks: 11086, 00 (IBD+Az) vs. 10485, 83 (IBD) (P < 0, 05), 11255, 25 (NDV+Az) vs. 8478, 75 (NDV) (P < 0, 05). Three weeks: 11478 (IBD+Az) vs. 8286 (IBD) (P < 0, 05), 14725 (NDV+Az) vs. 12677 (NDV) (P < 0, 05). Four weeks: 12999 (IBD+Az) vs. 1009, 67 (IBD) (P < 0, 05), 17399 (NDV+Az) vs. 16373, 17 (NDV) (P < 0, 05). Five weeks: 13601, 15 (IBD+Az) vs. 9021, 30 (IBD) (P < 0, 05), 19671 (NDV+Az) vs. 16309 (NDV) (P < 0, 05). Thus, Azaxul had a positive influence on the post-vaccination immune response in laying hens when used after Newcastle Disease and Infectious Bursal Disease vaccines. The results of the study can be used to improve disease prevention in poultry farming.